Quantifying the RNA cap epitranscriptome reveals novel caps in cellular and viral RNA. Issue 20 (2nd September 2019) - Wang, Jin; Alvin Chew, Bing Liang; Lai, Yong; Dong, Hongping; Xu, Luang; Balamkundu, Seetharamsingh; Cai, Weiling Maggie; Cui, Liang; Liu, Chuan Fa; Fu, Xin-Yuan; Lin, Zhenguo; Shi, Pei-Yong; et al.
Abstract: Chemical modification of transcripts with 5′ caps occurs in all organisms. Here, we report a systems-level mass spectrometry-based technique, CapQuant, for quantitative analysis of an organism's cap epitranscriptome. The method was piloted with 21 canonical caps—m 7 GpppN, m 7 GpppNm, GpppN, GpppNm, and m 2, 2, 7 GpppG—and 5 'metabolite' caps—NAD, FAD, UDP-Glc, UDP-GlcNAc, and dpCoA. Applying CapQuant to RNA from purified dengue virus, Escherichia coli, yeast, mouse tissues, and human cells, we discovered new cap structures in humans and mice (FAD, UDP-Glc, UDP-GlcNAc, and m 7 Gpppm 6 A), cell- and tissue-specific variations in cap methylation, and high proportions of caps lacking 2′- O -methylation (m 7 Gpppm 6 A in mammals, m 7 GpppA in dengue virus). While substantial Dimroth-induced loss of m 1 A and m 1 Am arose with specific RNA processing conditions, human lymphoblast cells showed no detectable m 1 A or m 1 Am in caps. CapQuant accurately captured the preference for purine nucleotides at eukaryotic transcription start sites and the correlation between metabolite levels and metabolite caps.